Comparison of physical fitness tests and special judo fitness test performance and classificatory tables development for juvenile and cadet male athletes - Monteiro, L.; Veloso, R.; Hormigo, A.; Louro, A.; Saldanha, P.; Silva, T.; Nogueira, P. (Journal of Human Sport & Exercise, 2019)
The aims of this work were to compare the performances of juvenile and cadet male judo athletes and to develop classificatory tables to these judo-specific tests for national and international-level of Portuguese athletes from these ages. Data collected during training camps (2017-2018) of male juvenile and cadet judo from Clubs and National team of Portugal were analysed, totalizing 430 individual results of Special Judo Fitness Test (SJFT), and Physical Fitness Tests (PFT), Beeps Test (BT), VO2máx, Sit-ups 1 min, Push-ups, Hand Grip Strength (HGS), Squat Jump (SJ), Countermovement Jump (CMJ), Standing Broad Jump (SBJ) and Sit and Reach (S&R) respectively. Cadets performed better than juvenile in the SJFT, with higher number of throws in A, B, C (P< 0.01) for all comparisons final heart rate (P= 0.05), and index (P< 0.001), as well as higher performance in the PFT (P< 0.001). Considering these differences, tables were established by age groups, using percentile values. Thereby, each of the parameters of the SJFT (number of throws, heart rate after and 1 min after the test, and SJFT index), as well as absolute results in PFT, were classified by age (juvenile and cadet). These classificatory tables can be useful for judo coaches to monitor specific physical performance during different phases of periodization process and individualize training programs for successful long-term athletic development.